A systematic and critical review on the research landscape of finance in Vietnam from 2008 to 2020 - Tung Manh Ho; Ngoc-Thang B. Le; Tran Hung-Long D.; Quoc-Hung Nguyen; Manh-Ha Pham; Minh-Hoang Ly; Manh-Toan Ho; Minh-Hoang Nguyen; Quan Hoang Vuong (Journal of Risk and Financial Management, 2021)
This paper endeavors to understand the research landscape of finance research in Vietnam during the period 2008 to 2020 and predict the key defining future research directions. Using the comprehensive database of Vietnam's international publications in social sciences and humanities, we extract a dataset of 314 papers on finance topics in Vietnam from 2008 to 2020. Then, we apply a systematic approach to analyze four important themes: Structural issues, Banking system, Firm issues, and Financial psychology and behavior. Overall, there have been three noticeable trends within finance research in Vietnam: (1) assessment of financial policies or financial regulation, (2) deciphering the correlates of firms' financial performances, and (3) opportunities and challenges in adopting innovations and ideas from foreign financial market systems. Our analysis identifies several fertile areas for future research, including financial market analysis in the post-COVID-19 eras, fintech, and green finance.
Keywords: 330; banking; finance; financial market; financial psychology; financial system; Vietnam